PENGARUH CURRENT RATIO, QUICK RATIO, NET PROFIT MARGIN TERHADAP PERUBAHAN LABA PADA PT. PP (TBK): PENGARUH CURRENT RATIO, QUICK RATIO, NET PROFIT MARGIN TERHADAP PERUBAHAN LABA PADA PT. PP (TBK) - Darmeinis; Menik Sarwini (Jurnal Publikasi Manajemen Informatika, 2022)
This study aims to determine the effect of liquidity ratios and the effect of profitability ratios on profit changes at PT. PP (Tbk). In this study, the liquidity ratio is measured by the Current Ratio (CR) and Quick Ratio (QR), while the profitability ratio is by the Net Profit Margin (NPM). The population in this study is the financial data report of PT. PP (Tbk) for 23 years, from 1998-2020 which can be accessed at www.ptpp.co.id. The sample of this research is the company's financial data reports for 15 years from 2006-2020 using the purposive sampling method. Analysis of research data used is a multiple linear regression analysis techniques. The results showed that partially CR, QR, and NPM have no significant effect on changes in company profits. This is evidenced by the CR significance value of 0.674 > 0.05, the QR significance value is 0.175 > 0.05 and the significance value of NPM is 0.838 > 0.05. Simultaneous test results also show that CR, QR, and NPM have no significant effect on changes in company profits, as evidenced by a significance value of 0.119 > 0.05. The coefficient of determination results showed that only 40% of profit changes are influenced by CR, QR, and NPM, while the remaining 60% are affected by other factors not examined in the study.